SUMBANGAN HANS KÜNG DAN EMMANUEL LEVINAS TERHADAP KONSEP KERUKUNAN UMAT BERAGAMA - Rosmaria Sjafariah Widjajanti (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
Hans Küng stated that peace between religions to be a prerequisite for world peace. In this life there will be no peace without peace between religions. There is no peace between religions without dialogue between religions, and there is no dialogue between religions without accurate knowledge of each other. According to Levinas, interfaith dialogue occurs because people must be able to appreciate religious pluralism, cultural diversity, and attention to conflicts between religions and cultures. Each religion and culture has had a uniqueness that must be recognized and accepted.